PEMBERDAYAAN PEMUDA MELALUI PELATIHAN MC DAN PROTOKOL DI MASJID DARUL MA’ARIF KOTA MAKASSAR - Muhammad Aksan; Muhammad Agus Budiawan (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2025)
This activity was carried out at the Darul Ma'arif Mosque, Makassar, for two days using mentoring methods and learning by doing simulations. A total of 12 mosque teenagers actively participated in the training, which included providing materials, direct practice, and question and answer sessions. Participants are given the opportunity to practice the MC role based on a script prepared by the training team. The pre-test results showed that after the training, participants' self-confidence increased significantly to 83.3%. Apart from increasing self-confidence, this training was also successful in expanding participants' knowledge about public speaking techniques and the importance of the MC's role in supporting social and religious activities to become active agents of change in religious and social activities as the next generation for nation and state development.